Comprehensive Overview on Antibody Drug Conjugates- A Promising Approach in Cancer Therapy - Muppa, Lenna; Ravindranathan, Shruthi; Sivaram, S; Jinnah, Aadhira; Shibu, Achsa Sharon (Journal of Drug Delivery and Therapeutics, 2025)
Chemotherapy remains a cornerstone in cancer treatment, utilizing cytotoxic agents to kill or inhibit the growth of cancer cells. However, its efficacy is often limited by systemic toxicity and the development of resistance. To address these challenges, Antibody-Drug Conjugates (ADCs) have emerged as a promising therapeutic strategy, combining the specificity of monoclonal antibodies with the potency of cytotoxic drugs. ADCs are designed to deliver targeted chemotherapy directly to cancer cells, reducing off-target effects and improving therapeutic outcomes. The structure of ADCs consists of a monoclonal antibody, a cytotoxic agent (payload), and a chemical linker. The antibody specifically binds to tumor-associated antigens, facilitating internalization of the drug, which is then released within the cancer cell to induce cell death. This selective targeting minimizes the damage to normal, healthy tissues. Since the first ADC approval in 2000, the field has rapidly advanced, with multiple ADCs receiving FDA approval for both hematological and solid tumors. Despite their potential, ADC development faces challenges such as linker stability, payload delivery, and tumor penetration. Recent advancements have led to the development of second and third-generation ADCs, which feature improved stability, efficacy, and safety profiles. The future of ADCs lies in optimizing their design, including selecting appropriate antigens, refining drug-to-antibody ratios, and enhancing intracellular delivery mechanisms. Overall, ADCs represent a transformative approach to cancer therapy, offering a more targeted, effective, and safer treatment option for cancer patients.Keywords: ADC, Cancer, Chemotherapy, Cytotoxic drug, Carrier, Linker, Target therapy, Toxicity.